KONSEP SEDEKAH KOLEKTIF BERHADIAH BERDASARKAN HUKUM EKONOMI SYARI’AH (Muamalah, 2022)
The journal entitled: "A Study of the Concept of Collective Alms with Berhadah Based on the Perspective of Sharia Economic Law (Study at the Agency for Personnel and Human Resources Development of Palembang City)" With the background of the problem that the concept of collective alms with prizes designed by the Agency for Personnel and Human Resources Development (BKPSDM) Palembang City is different from the concept of alms in general which is often done individually, without being limited by time and a certain amount spontaneously and voluntarily. The thing that distinguishes the alms program at the Personnel and Human Resources Development Agency of Palembang City and alms in general lies in the giving of one Umrah package as a gift to the selected alms member as a reward. The formulation of the problem in this study is first, How is the concept of collective alms with prizes at the Personnel and Human Resources Development Agency (BKPSDM) of Palembang City? Second, what is the perspective of Sharia Economic Law on the concept of collective alms with prizes at the Personnel and Human Resources Development Agency (BKPSDM) of Palembang City? This research method uses the type of field research (Field Research) which was carried out at the BKPSDM Palembang City. The data collection method in this research is through interviews and documentation. Sources of data used in this study are primary data sources obtained through interviews with the Head of the Agency and Staff/Employees at BKPSDM Palembang City, and secondary data sources obtained from books and research results related to the discussion in this study. The data analysis used by the author in this study is qualitative descriptive. The results of the study concluded that the concept of collective alms with prizes at the Palembang City BKPSDM was carried out voluntarily and put forward the concept of honesty, the money from alms was issued in the form of gifts in the form of Umrah as a reward to selected employees. Based on the perspective of Sharia Economic Law, the concept of collective alms with prizes is in accordance with the principles of Sharia Economic Law because the alms are done voluntarily, which means that there is no coercion from any party and is not carried out for profit. The contract used in this alms concept is the tabbaru contract (please help), the alms issued in the form of umrah gifts are a form of mutual assistance among employees, and to motivate the Palembang City BKPSDM employees to be fond of giving alms. Keywords: Alms Concept, Prize, Sharia Economic Law